AN ANALYSIS OF PREJUDICE IN TAYARI JONES’S NOVEL AN AMERICAN MARRIAGE - Widi Ambarwati; Siti Norma Nasution (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study entitled "An Analysis Of Prejudice As Portrayed In Tayari Jones's Novel An American Marriage". In this study the writers analyzes the forms of prejudice namely stereotype, social distance, and discrimination. This study aims to reveal that literary works reflect to social reality. The object of this study is a novel entitled "An American Marriage". In this study the writers has three problems to discuss: how is the stereotype as form of prejudice portrayed in Tayari Jones’s novel An American Marriage, how is the social distance as form of prejudice portrayed in Tayari Jones’s novel An American Marriage, and how is the discrimination as form of prejudice protrayed in Tayari Jones’s novel An American Marriage. This study used a qualitative descriptive method. Data is obtained from words, phrases, clauses or sentences that relate to stereotype, social distance and discrimination.